Contextual Mapping of Students’ Leadership Traits for School Character Development Programs in Indonesia - Nurjaya Nurjaya; Abdul Mu'ti; Sapiudin Sapiudin; Yanti Herlanti; Suwendi Suwendi; Septian Arief Budiman (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to map students’ leadership traits within the context of school character development programs in Indonesia, addressing the absence of a systematic framework for identifying and integrating leadership characteristics into character education practices. Conducted as a qualitative case study, the research involved three secondary schools: SMP Islam Al-Ikhlas Cipete (South Jakarta), SMPIT Darojatul Uluum (Depok), and SMPIT Al-Husain (Tangerang), all selected for their active, character-based educational environments. Data were collected through in-depth interviews, participant observations, and document analysis involving school principals, teachers, student organization advisors, and selected student leaders. Thematic analysis was used to identify patterns of leadership traits across the three school contexts. The findings indicate that students demonstrate a range of core leadership traits, including responsibility, communication skills, initiative, empathy, and collaborative orientation, which emerge differently depending on school culture, mentorship practices, and program structure. The study also reveals contextual variations, including the influence of Islamic values, peer-led activities, and teacher modeling on leadership expression. The conclusion highlights that contextual mapping enables a more targeted, responsive approach to character development by aligning program components with students’ existing leadership potential. The implications suggest that schools should adopt a structured leadership-trait identification model to inform program design, strengthen teacher mentoring strategies, and enhance student agency in character-building activities. The study further contributes to theoretical discussions on contextualized student leadership frameworks within character-based education in Indonesian secondary schools.